A redox-activated G-quadruplex DNA binder based on a platinum(IV)-salphen complex - Vilar,R; Bandeira,S; Gonzalez,Garcia J; Pensa,E; Albrecht,T (Angewandte Chemie International Edition, 2017)
There has been increasing interest in the development of small molecules that can selectively bind to G-quadruplex DNA structures. The latter have been associated to a number of key biological processes and therefore are proposed to be potential targets for drug development. In this paper we report the first example of a reduction-activated G-quadruplex DNA binder. We show that a new octahedral platinum(IV)-salphen complex does not interact with DNA in aqueous media at pH 7.4; however, upon addition of bio-reductants such as ascorbic acid or glutathione, the compound readily reduces to the corresponding square planar platinum(II) complex. In contrast to the parent platinum(IV) complex, the in situ generated platinum(II) complex binds to HTelo and c-Myc G-quadruplex DNA with affinity constants up to 106 M-1.